Outcome of low level lasers versus ultrasonic therapy in de Quervain's tenosynovitis - Sharma, Renu (Indian J Orthop, 2015)
BACKGROUND: de Quervain's tenosynovitis is an inflammation of abductor pollicis longus (APL) and extensor pollicis brevis (EPB) muscle tendon sheaths at the level of radial styloid process. Its conservative management includes nonsteroidal anti-inflammatory drugs, wrist and thumb immobilization, ultrasonic therapy (US Th.) and low level laser therapy (LLLT). Literature is scanty on comparative efficacy of US Th. and LLLT for its management. This prospective study evaluates outcome of US Th. versus LLLT in de Quervain's disease. MATERIALS AND METHODS: Thirty patients clinically diagnosed de Quervains tenosynovitis were included in the study and randomly assigned to two groups. The average age was 36 years (range: 21-45 years). One group was given LLLT and the other US Th. for a total of 7 exposures on alternate days. The clinical criteria used were Finkelstein's test, tenderness over radial styloid (Ritchie's tenderness scale), grip strength, pain (visual analog scale [VAS]) and radiological criteria was ultrasonographic assessment of change in thickness of APL and EPB tendon sheath. They were measured before commencement and at the end of seven sessions of therapy, as per standard procedure. RESULTS: Significant improvement was seen within both groups in the following outcome measures assessed: Ritchie's tenderness scale, grip strength and VAS. Finkelstein's test was not significantly improved in either groups. Ultrasonographic measurement of tendon sheath diameters, the mediolateral (ML), and anteroposterior (AP) diameters was not found to be significantly different in the US Th. group and the laser therapy group after treatment. On comparing both the groups, no statistically significant difference was found. However, looking at the mean values, the grip strength and VAS showed better improvement in the US Th. group as compared to the laser therapy group.